Peran Kepala Desa dalam Mewujudkan Kesejahteraan Masyarakat Miskin melalui Peraturan Desa - Musfianawati Musfianawati (JURNAL RECHTENS, 2015)
Poverty is a problem experienced by almost all developing countries, especially countries which amounts to a large population. For Indonesia, poverty is a national problem, so the government is attempting to solve the problem of poverty with various programs. However, in general, the results of the program can not be said to be significant, because in many places, the number of poor people is increasing. Problems with various characteristics of poverty is not easily solved without the involvement of all elements. Because, the primary key of the efforts to reduce poverty in the region is the establishment, as well as the institutionalization of network communication, coordination and cooperation of the three pillars in the area: local government, community and care groups (NGOs, private sector, universities, religious / community leaders, and the press ). The problems of poverty can only be addressed if the three components on mutual cooperation in the spirit of togetherness, and participate to find alternative solutions. The role of village heads in rural building into a central point and become very large, because the village has been given the authority to set their own communities to be able to be independent. This is a big change in the history of governance. Significant changes occurred at the time of the enactment of Law No. 6 in 2014, about the village, which give rise to various development policies and poverty reduction patterns. Act No. 6 of 2014 on village mengamanahkan a very significant role to the figure of the village head. The village head as the government has considerable authority in determining policy in the village, it is supposed that the welfare of rural communities depends on the role of a village head. In the welfare of the community, the village chief can use his role to make policies in writing as outlined in the village regulations.